ANALYSIS OF THE CHANCE OF THE FINANCIAL DISTRESS ON TELECOMUNICATION COMPANIES LISTED ON INDONESIA STOCK EXCHANGE (IDX) - Siti Alyfah Ainun Putri Baramuli; Mursalim Nohong; Muhammad Ali (Paulus Journal of Accounting (PJA), 2023)
Financial distress is the process by which a company goes through a deterioration in its financial condition before it may face bankruptcy or liquidation. This study uses the Altman Z-Score approach to forecast the financial distress of telecommunication corporations listed on the Indonesia Stock Exchange (IDX) from 2009 to 2019. The study used secondary data from the financial reports of PT Telkom Indonesia (Persero) Tbk, PT XL Axiata Tbk, and PT Indosat Tbk. The analysis method used was Altman Z-Score correction. The independent variables included working capital and total assets (X1), Retained earnings as a percentage of total assets (X2), EBIT as a percentage of total assets (X3), and the ratio of market value of equity to book value of liabilities (X4). The dependent variable is financial distress (Y). The research findings indicate the following: 1) The Effect of Working Capital on Total Assets, as measured by the relationship between working capital and total assets; 2) Effect of Retained Earnings to Total Assets on Financial Distress; 3) Effect of Earning Before Interest and Taxes to Total Assets on Financial Distress; and 4) Effect of Market Value of Equity to Book Value of Liabilities on Financial Distress.